Analgesic and Anti-Inflammatory Effects of Perampanel in Acute and Chronic Pain Models in Mice: Interaction With the Cannabinergic System - De Caro, Carmen; Cristiano, Claudia; Avagliano, Carmen; Cuozzo, Mariarosaria; La Rana, Giovanna; Aviello, Gabriella; De Sarro, Giovambattista; Calignano, Antonio; Russo, Emilio; Russo, Roberto (Frontiers in Pharmacology, 2021)
Pain conditions, such as neuropathic pain (NP) and persistent inflammatory pain are therapeutically difficult to manage. Previous studies have shown the involvement of glutamate receptor in pain modulation and in particular same of these showed the key role of the AMPA ionotropic glutamate receptor subtype. Antiseizure medications (ASMs) are often used to treat this symptom, however the effect of perampanel (PER), an ASM acting as selective, non-competitive inhibitor of the AMPA receptor on the management of pain has not well been investigated yet. Here we tested the potential analgesic and anti-inflammatory effects of PER, in acute and chronic pain models. PER was given orally either in acute (5 mg/kg) or repeated administration (3 mg/kg/day for 4 days), Pain response was assessed using models of nociceptive sensitivity, visceral and inflammatory pain, and mechanical allodynia and hyperalgesia induced by chronic constriction injury (CCI) to the sciatic nerve. PER significantly reduced pain perception in all behavioral tests as well as CCI-induced mechanical allodynia and hyperalgesia. This effect was also observed after repeated treatment using the dose of 3 mg/kg/day. The antinociceptive, antiallodynic and antihyperalgesic effects of PER were attenuated when the CB1 antagonist AM251 (1 mg/kg/i.p.) was administered before PER treatment, suggesting the involvement of the cannabinergic system. Moreover, Ex vivo analyses showed that PER significantly increased CB1 receptor expression and reduced inflammatory cytokines (i.e. TNFα, IL-1β, and IL-6) in the spinal cord. In conclusion, these results extend our knowledge on PER antinociceptive and antiallodynic effects and support the involvement of cannabinergic system on its mode of action.